Synthesis and Antimicrobial Activity of s-Triazine Based Chalcones, Pyrazolines and Amino Pyrimidines - Solankee, Anjani; Kapadia, Kishor; Lad, Smurti; Patel, Jayesh; Thakor, Indrajit (Asian Journal of Chemistry, 2016)
Some s-triazine based chalcones have been synthesized starting from ketone (D) and different aldehydes. Chalcones on cyclization with hydrazine hydrate and guanidine nitrate give the corresponding pyrazolines and amino pyrimidines. The synthesized compounds are screened for their antimicrobial activity. The structures of the synthesized compounds have been confirmed by elemental analysis, IR and NMR spectral studies.